Exchange Rate Pass-Through Asymmetry: The Case of the Euro-Zone - Stojkov, Stefan; Beker Pucar, Emilija; Glavaški, Olgica; Beljić, Marina (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
An essential aspect of deepening the level of economic integration between European economies is the reduction of mutual economic disparities, which is especially emphasized by the formation of the supranational monetary authority of the Euro-zone member states. However, fixing the currency for the euro and losing monetary sovereignty in the circumstances of a structurally heterogeneous system meant that the same monetary policy provoked different repercussions for member states. This research aims to point out the differences in the exchange rate transmission mechanism between the representatives of two groups of Euro-zone member states: the core of the EZ (Germany, Finland, Belgium, and France) and the periphery of the EZ (Greece, Spain, Portugal, Ireland), in the 1999M1-2021M1 time horizon. Empirical findings are based on estimates of the VAR model, i.e. derived impulse response functions in the circumstances of shock transmission (nominal effective exchange rate) to inflation (consumer price index). The results of the research indicate the asymmetry of the exchange rate transmission mechanism in terms of a more pronounced and longer degree of exposure of peripheral economies to shocks of the nominal exchange rate compared to the representatives of the core of the Euro-zone. Empirical findings confirm the asymmetry of the exchange rate transmission mechanism as one of the indicators of the weakness of the Euro-zone, given the inflationary diversity and the consequent anomalies of the monetary union with heterogeneous membership.